THE ROLE OF THE TOURISM SECTOR ON THE ECONOMY OF EAST JAVA: INPUT-OUTPUT ANALYSIS - Eka Andri Kurniawan (East Java Economic Journal, 2018)
Indonesia is a country that regulates the authority of regional government. Local governments are given the freedom to regulate their own regions with regionalautonomy to explore the potential of each region. Thus, development must determine the priority of the potential of one of the tourism sector. For examplecultural tours, history, nature or artificial, religious. Tourism is a large and growing industry. The development of tourism is very influential and influenced by other sectors because tourism is a mulitectorectoral that has links with other sectors. East Java province is renowned for its tourism potential, many historical attractions, for recreation, education and more. The development and change of the tourism sector cannot be separated from the interrelationship with other sectors of the economy, and vice versa. The occurrence of changes in one sector of the economy, will also affect the tourism sector. The inter-sectoral linkages in the economy can be seen in Input-Output Analysis. Input-Output Analysis is an analysis of the region's economy comprehensively as it sees the inter-sectoral linkages of the economy in the region as a whole. This study aims to find out how the role of the tourism sector in the formation of output, gross added value, demand between and end of East Java Province, how much is related to other sectors, the economic impacts of economic growth, income and employment are viewed based on Multiplier effects on output, income and labor. The data collected in this study is secondary data Table InputOutput East Java Province. Analyzer uses APLIKASI I-O PAU UGM 2000 and Microsoft Excel. The result, it is expected that the tourism sector has an important role in the formation of GDP, labor, demand between and the end of demand, as well as direct output linkage forward.